P0431TRENDS OF PRIMARY GLOMERULAR DISEASE IN TURKEY FROM 2009 TO 2017: A REGIONAL REGISTRY REPORT FROM TSN-GOLD WORKING GROUP. (6th June 2020) - Gul, Cuma Bulent; Kucuk, Mehmet; Ozturk, Savas; Demir, Erol; Eren, Necmi; Sumnu, Abdullah; Seyahi, Nurhan; Gullulu, Mustafa; Dede, Fatih; Derici, Ülver; Koc, Yener; SAHIN, Garip; et al.
Abstract: Background and Aims: Several glomerular disease registries in Europe, and they shared their data; however, there was a lack of current data on trends of primary glomerulopathy in Turkey. Glomerular disease patterns can change geographical areas and populations decade by decade. Our aim is to present Turkey's primary glomerular disease pattern from 2009 to 2017. Method: 3878 native kidney biopsy records were assessed in the Turkish Society of Nephrology Glomerulopathy (TSN-GOLD) Working Group Registry. Secondary disease (lupus, etc.) and transplant biopsies do not enroll in the registry. These records divided into four periods, before 2009, 2009 to 2013, 2013 to 2017, and 2017 to current. Results: A total of 3858 patients (M = 2173, K = 1685) were examined. There was no difference in the distribution of number of patients according to periods (Q1 = 968, Q2 = 960, Q3 = 968, Q4 = 962). Nephrotic syndrome was the most common biopsy indication in all quarters (58.6%, 53%, 44.1%, 51.6%, respectively). Glomerulopathy types; Membranous GN (29.9%, n = 290) was the first in Q1 and IgA nephropathy (17.7%, n = 172) was the second. IgA nephropathy (28.5%, n = 274) was the most common glomerulopathy in Q2, while Membranous GN (25.5%, n = 245) was the second most common. IgA nephropathy (29.9%, n = 285) was the most common glomerulopathy in Q3, followed by FSGS (22.9%, n = 222) and Membranous GN. In Q4, FSGS (26.8, n = 258) was the most common glomerulopathy, followed by IgA nephropathy (26.7%, n = 257) and Membranous GN (24.5%, n = 236) (Figure 1). Conclusion: While biopsy indications did not change over the years, the incidence of FSGS and IgA nephropathy gradually increased.